STATIC RESERVOIR MODELING AND ORIGINAL HYDROCARBON IN-PLACE ESTIMATION OF KUJUNG FORMATION, MARINA FIELD, NORTH EAST JAVA BASIN - Noor Zafira, Afra
Marina field is an onshore oil and gas field on development stage. The field located administratively in East Java Province. Geogically, Marina field located in Tertiary aged-North East Java Basin. This study takes focus on Kujung Formation, with one reservoir interval consisting limestone as its lithology. The aim of this study is to determine static model of the reservoir and to estimate the reservoir’s original hydrocarbon in-place. Data used in this study consists of wireline log, 3D seismic, core data, and well test data. Several methods used in this study are, well data analysis that includes well correlation, facies analysis, facies association and depositional environment analysis, and petrophysics analysis; seismic data analysis that includes seismic fasies analysis and determinating the depth structure map and isopach map; static reservoir modeling that includes 3D structure modeling, petrophysical modeling, oil-water contact, and the estimation of original hydrocarbon in place. The results after implying those methods are the geological setting and the estimation of its hydrocarbon in-place in Marina Field. Facies analysis based on core description and petrography data shows 5 lithofacies that are Skeletal Packstone (Sp), Algal Bindstone (Ab), Skeletal Wackestone (Sw), Skeletal-Peloid Packstone (Spp), Peloid-Skeletal Packstone (Psp). Those lithofacies composing two facies associations as well as the depositional environment which is platform margin reef and platform interior. The estimated hydrocarbon in-place (OOIP) from the reservoir is 130.89 MMSTB.